2020
DOI: 10.1021/acs.organomet.0c00091
|View full text |Cite
|
Sign up to set email alerts
|

NHC-Palladium(II) Mononuclear and Binuclear Complexes Containing Phenylene-Bridged Bis(thione) Ligands: Synthesis, Characterization, and Catalytic Activities

Abstract: A series of mono- and binuclear Pd­(II) complexes with N-heterocyclic carbene (NHC) and phenylene-bridged bis­(thione) (SCS) ligands were prepared and characterized by 1H and 13C NMR spectroscopy, IR, and mass spectrometry. The molecular structures of 1b, 2a, and 3b have been determined by the single-crystal X-ray diffraction method. The catalytic activities of the synthesized palladium complexes in the regioselective reduction of quinolines to the corresponding 1,2,3,4-tetrahydroquinolines were thoroughly inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…NMR spectra were recorded on a Bruker AVANCE III HD 600 spectrometer ( 1 H NMR: 600 MHz. 13 C NMR: 151 MHz) and Bruker AVANCE III HD 400 spectrometer ( 1 H NMR: 400 MHz.). Chemical shifts (δ) for 1 H NMR and 13 C NMR spectra are given in ppm relative to the internal standard tetramethylsilane (TMS).…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…NMR spectra were recorded on a Bruker AVANCE III HD 600 spectrometer ( 1 H NMR: 600 MHz. 13 C NMR: 151 MHz) and Bruker AVANCE III HD 400 spectrometer ( 1 H NMR: 400 MHz.). Chemical shifts (δ) for 1 H NMR and 13 C NMR spectra are given in ppm relative to the internal standard tetramethylsilane (TMS).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…13 C NMR: 151 MHz) and Bruker AVANCE III HD 400 spectrometer ( 1 H NMR: 400 MHz.). Chemical shifts (δ) for 1 H NMR and 13 C NMR spectra are given in ppm relative to the internal standard tetramethylsilane (TMS). The residual solvent signals were used as references for 1 H NMR and 13 C NMR spectra and the chemical shifts converted to the TMS scale (CDCl 3 : δ H = 7.26 ppm.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are a few systems reported that can catalyze the transfer hydrogenation of quinoline derivatives with AB. [27][28][29][30][31][32][33] In homogeneous catalytic systems, several examples employing frustrated lewis pairs B(C 6 F 5 ) 3 , [27] Ni II -bis(pyrazolyl)pyridine, [28] cupric sulfate, [29] zirconium-hydride complex, [30] and Pd II complex [31] have been disclosed. Because of the chemically stable and easy to handle natures of heterogeneous catalysts, they have also been applied in the hydrogenation of quinolines with AB.…”
Section: Introductionmentioning
confidence: 99%
“…Çetinkaya and co-workers have reported Pd-NHC catalyzed C (sp 2 )ÀH bond activation reaction in 2005 [36]. Also, Doucet, Shao, Xu and Özdemir groups reported Pd-NHC complexes that showed important activity in C-H bond activation reactions [37][38][39][40][41][42][43][44][45][46][47]. C-H bond activation reactions of substituted thiazoles have been reported by various groups [35,47].…”
Section: Introductionmentioning
confidence: 99%